2015
DOI: 10.1038/nature14987
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneity of charge-density-wave order and quenched disorder in a high-Tc superconductor

Abstract: It has recently been established that the high temperature (high-Tc(between atomic and macroscopic scale). Here we report micro X-ray diffraction imaging of the spatial distribution of both the charge-density-wave 'puddles' (domains with only a few wavelengths) and quenched disorder in HgBa 2 CuO 4+y , the single layer cuprate with the highest T c , 95 kelvin [26][27][28] . We found that the charge-density-wave puddles, like the steam bubbles in boiling water, have a fat-tailed size distribution that is typica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

39
327
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 301 publications
(370 citation statements)
references
References 32 publications
39
327
2
2
Order By: Relevance
“…The relationship between the charge order and the superconductivity is not a simple mutual exclusion as also noticed very recently for high temperature superconductivity 44 . Moreover, this…”
supporting
confidence: 53%
“…The relationship between the charge order and the superconductivity is not a simple mutual exclusion as also noticed very recently for high temperature superconductivity 44 . Moreover, this…”
supporting
confidence: 53%
“…These inhomogeneous phases are due to the ordering of dopants and competition between short range charge, spin and orbital density wave order (CDW, SDW, ODW) inhomogeneity. As a result, new complex geometries emerge, where quantum coherence develops [12][13][14]. Thus, the study of local features by using high resolution experimental probes assumes a paramount importance for the a deeper understanding of new complex and heterogeneous materials.…”
Section: Introductionmentioning
confidence: 99%
“…The collected data, treated by spatial statistical tools, have shown the formation of fractal patterns of interstitial oxygens ordered domains in LCO [21], intrinsic phase separation in doped iron-chalcogenides [22,23] and planar symmetry breaking in Bismuthates [24]. More recently, it's has been demonstrated that the quenched disorder due to dopants is spatially anticorrelated with electronic textures and/or local lattice distortions in Hg1201 [12,13] and LCO [25]. Thus, the oxygen striped domains are candidate to provide the space where superconductivity arises.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The misfit strain between the spacer layers on the FeAs layers occurs [13] inducing an anisotropic internal pressure on the FeX layers which together with a proximity to a Lifshitz transition driven by a new appearing Fe 3d small Fermi surface pocket [14,15] gives a particular inhomogeneity giving nanoscale phase separation like in cuprates [15][16][17][18][19] which has been investigated by XANES [20][21][22] and predicted for Lifshitz transition in multiband Hubbard model [23,24]. From the application point of view, it is very important to explore this complex disorder controlled by space layers in the superconducting properties, such as the flux-pinning as it was made recently in cuprates [25].…”
Section: Introductionmentioning
confidence: 99%